( | x | − | 7 | ) | ÷ | 5 | = | 1 | − | ( | 2 | x | + | 2 | ) | ÷ | 3 |
Left side of the equation = | x | × | 1 5 | − | 7 | × | 1 5 |
= | x | × | 1 5 | − | 7 5 |
1 5 | x | − | 7 5 | = | 1 | − | ( | 2 | x | + | 2 | ) | ÷ | 3 |
Right side of the equation = | 1 | − | 2 | x | × | 1 3 | − | 2 | × | 1 3 |
= | 1 | − | 2 3 | x | − | 2 3 |
= | 1 3 | − | 2 3 | x |
1 5 | x | − | 7 5 | = | 1 3 | − | 2 3 | x |
1 5 | x | + | 2 3 | x | = | 1 3 | + | 7 5 |
13 15 | x | = | 1 3 | + | 7 5 |
13 15 | x | = | 26 15 |
x | = | 26 15 | ÷ | 13 15 |
= | 26 15 | × | 15 13 |
= | 2 | × | 1 |
x | = | 2 |